The impacts of oil price shocks and United States economic uncertainty on global stock markets. (21st August 2020) - Kwon, Dohyoung
Abstract: This article examines interdependence between oil price shocks and United States economic uncertainty and their effects on global stock markets within a structural VAR model over the last 40 years. I find that aggregate demand shocks cause a transitory rise in global real stock returns, whereas precautionary oil demand and United States economic uncertainty shocks decline the returns. Especially, oil demand shocks significantly increase United States economic uncertainty, indicating that their direct impacts on global stock markets are amplified by its endogenous response. Variance decomposition analysis shows that oil price shocks and United States economic uncertainty explain 17% and 6% of long‐run variations in global real stock returns, respectively. These figures have more than tripled when the model is estimated on post 2000 data, suggesting that oil market fundamentals and United States macro uncertainty are an important determinant of global stock market movements.